Soil seed bank dynamics and vegetation composition in raudhat Altinhat, Saudi Arabia: implications for arid ecosystem restoration - Abd-ElGawad, Ahmed M.; Al-Huqail, Asma A.; Alowaifeer, Abdullah M.; Alsaleem, Turki S.; Assaeed, Abdulaziz M.; Azab, Omar M.; Dar, Basharat A.; Kassem, Hazem S. (Frontiers in Environmental Science, 2025)
The soil seed bank (SSB) composition is crucial for ecosystem vitality and restoration. The present study aimed to evaluate the SSB and vegetation composition in Raudhat Altinhat, Saudi Arabia, an arid ecosystem. A total of 14 plots were determined and studied for their aboveground vegetation during winter-spring and summer-fall seasons. Soil samples were collected for chemical and physical analyses to determine the edaphic factors affecting vegetation composition. Soil sample of 4000 cm3 was collected and analyzed for SSB composition via direct emergent method. Eighty-six plant species (55.8% annuals and 44.2% perennials) were determined in aboveground vegetation. Asteraceae, Poaceae, Boraginaceae, and Fabaceae were major families. During winter-spring season, communities of Ziziphus nummularia, Zilla spinosa-Rhazya stricta, and R. stricta were identified, where most of soil variables did not show significant variation among communities, except for salinity, Ca, Mg, SO4, and NO3. Also, during summer-fall season, communities of R. stricta, Z. nummularia, and Cynodon dactylon were identified, and most soil variables did not show significant variation among communities, except for Mg and SO4 contents. SSB collected during winter-spring season comprised 23 species, mainly annuals (87.0%). Trigonella stellata was the predominant plant in SSB (average of 465 seeds/m2), followed by Phalaris minor (167 seeds/m2). During summer-fall season SSB had 22 plants, mainly annual (86.4%), while C. dactylon, Launaea nudicaulis, and V. gerrardi were identified as perennials. Trigonella stellata is the most predominant plant (159 seeds/m2). A negative correlation was observed between aboveground vegetation and SSB composition during both seasons. The species diversity indexes showed that aboveground vegetation during winter-spring season attained higher species richness and evenness, compared to SSB. However, during summer-fall season, species richness of aboveground vegetation and SSB was consistent, while species evenness was higher for SSB compared to aboveground vegetation. Our results showed that Raudhat Altinhat site needed rehabilitation and strict protection against all unmanaged activities, such as overgrazing and logging. Z. nummularia community showed high degradation and very low regeneration, and no seed germination in SSB. Therefore, further study is needed to determine the causes of the degradation and the best way to rehabilitate and recruit this very important shrub.